THE USE OF FILM IN IMPROVING STUDENTS' LISTENING COMPREHENSION - Rifan Rahmawan, - (2011)
Listening has an essential role in learning English. A lot of students, in fact, still have problems in listening comprehension. This study tried to investigate an alternative way of teaching listening by using films. It also tried to investigate students' responses toward the use of film in learning listening. This study was quasi-experimental with pre-test and post-test nonequivalent groups design. The population was students of first grade of SMA 15 Bandung and the samples were the students of 10-9 as the experimental class and the students of 10-8 as the control class. The findings indicated that the use of film was not effective in improving students' listening comprehension. There was no significant difference of the means between the experimental class and the control class. However, based on the result of the questionnaire, the students gave positive responses toward the use of film in improving motivation and participation in the class.